Investigação da mielotoxicidade e do potencial indutor de morte celular de Synadenium umbellatum Pax. em células do tumor ascítico de Ehrlich - MOTA, Mariana Flávia da (2010)
In search of new antineoplasic agents natural products have played an important role, given that about 40% of available medicines in current treatments have been developed from natural sources, 25% approximately of plants. Synadenium umbellatum belongs to Euphorbiaceae family and is popularly known as "cola-nota", "avelós," "milagrosa", "cancerola", and the latex is empirically used in Brazil for the treatment of cancer. Preliminary studies have shown that the crude extract of the leaves of S. umbellatum has significant antitumor and antiangiogenic activity in vivo. In this study, we investigated the cytotoxicity and the mechanisms of apoptosis induction of S. umbellatum in Ehrlich ascitic tumor (EAT) cells, and the myelotoxic potential of this plant. The cytotoxicity studies were carried out by trypan blue exclusion and reduction of tetrazolium (MTT) tests. The mechanisms of apoptosis induction were investigated by light and fluorescence microscopy, immunocytochemistry and flow cytometry. Investigation of the myelotoxic potential was performed by clonogenic assay of colony forming units of granulocyte-macrophage (CFU-GM). The data were analyzed by analysis of variance (ANOVA) and a posteriori Tukey test (myelotoxicity) and by t test for all other assays. The means were considered statistically significant when P < 0.05. S. umbellatum was cytotoxic to EAT cells and the morphological analysis of these cells indicated that the plant extract treatment induced cell death by apoptosis. Apoptosis was also observed by increase on reactive oxygen species generation and in the concentration of intracellular Ca2+, alterations in mitochondrial membrane potential, phosphatydylserine externalization and activation of caspases 3, 8, and 9. S. umbellatum presented myelotoxicity to normal bone marrow cells in a concentrationdependent fashion. However, this toxicity was 8-fold lower than to tumor cells. The presented data showed that S. umbellatum had cytotoxic activity to EAT cells and induced these cells to apoptosis.